Public attitudes to the rights and community inclusion of people with intellectual disabilities: A transnational study. (October 2020) - Slater, Paul; McConkey, Roy; Smith, Ashlyn; Dubois, Lindsay; Shellard, Amy
Highlights: The general public in 17 countries mostly endorse the rights of people with ID. Comfort at meeting people with ID predicted support for rights and acceptance. Country status on equality and development indices affected personal attitudes. Organisations that demonstrate social inclusion mediate public perceptions. Abstract: Background: Public support for the rights of persons with intellectual disability (ID) and their acceptance in local communities has been rarely studied internationally and the variables associated with more positive attitudes remain to be confirmed. Aims: To develop and test a model that brought together personal, organisational and national predictors related to public attitudes that have been previously identified in past research. Methods and procedures: Self-completed, online surveys were undertaken with market research panels in 17 countries and in eight cities in the USA with a total of 36, 508 respondents who were representative in terms of gender and age. Path analysis was used to explore the inter-relationships among the predictor, possible mediating and outcomes variables. Outcomes and results: The resulting model was a good fit for the data. Support for the rights and community acceptance of people with ID was highest among university educated respondents, those who were comfortable at meeting people with ID and those living in countries with very high ratings on the Inequality Adjusted Human Development Index. Conclusions and implications: The model could guide further research into public attitudes alongside the development of interventions to promote more positive attitudes. Further research into the validity of the model is proposed.